Analysis Of Differences In Pregnant Women's Knowledge About Stunting Before And After Being Counseled Using Smart Posters By Posyandu Cadres Assisted By The 1000 Days Fund Foundation In Bayur Kidul Village For The Period Of May 2024 - Nurika Rahma; Suci Suharti Juhana; Anah Sugihanawati; Erina Windiany (Universitas STRADA Indonesia, 2024)
The stunting condition in Indonesia in 2023 is 21.5%, West Java 21.7%, Karawang 17.1%, Bayur Lor Health Center 1.3%, Bayur Kidul Village 2.2%. This research aims to determine the difference in pregnant women's knowledge about stunting before and after being given counseling using Smart Poster media by posyandu cadres assisted by the 1000 Days Fund Foundation in Bayur Kidul Village, Cilamaya Karawang for the period May 2024. The research method is Pre-Experiment Designs. The design is One Group Pre-test and Post-test Design. The sampling technique was total sampling with a total of 38 pregnant women. The instrument uses a questionnaire. Dependent variable: pregnant women's knowledge about stunting before and after being given counseling. Independent variables: age, education, occupation, gravida and family income.